2000
DOI: 10.1007/bf03167620
|View full text |Cite
|
Sign up to set email alerts
|

Image compression and chest radiograph interpretation: Image perception comparison between uncompressed chest radiographs and chest radiographs stored using 10∶1 JPEG compression

Abstract: We have assessed the effect of 10:1 Iossy (JPEG) compression on six board-certified radiologists' ability to detect three commonly seen abnormalities on chest radiographs. The study radiographs included 150 chest radiographs with one of four diagnoses: normal (n = 101), pulmonary nodule {n = 19), interstitial lung disease (n = 19), and pneumothorax (n = 11). Before compression, these images were printed on laser film and interpreted in a blinded fashion by six radiologists. Following an 8-week interval, the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…5,6 Although image quality is the primary consideration, a risk versus bene®t analysis should consider other factors as well when deciding whether to use irreversible compression in clinical practice. The following additional factors should be considered:…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Although image quality is the primary consideration, a risk versus bene®t analysis should consider other factors as well when deciding whether to use irreversible compression in clinical practice. The following additional factors should be considered:…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have found that diagnostic information may be preserved on digitized chest radiographs at levels as high as 20 to 25:1 allowing diagnosis of interstitial ®brosis, pneumothorax, and detection of lung nodules. 1,5,18 Others have evaluated image compression in digital mammography 13,20 and coronary angiography. 3,17 To date, an optimal compression rate has neither been established nor are the criteria that might be used to determine such optimum de®ned.…”
Section: Discussionmentioning
confidence: 99%
“…Mori and Nakata 27 proposed a ratio of 25:1 with Az of 0.883 for chest image compression. Aberle et al 28 and Beall et al 11 conducted similar works to detect lung nodules in compressed chest images and reported ratios of 20:1 and 10:1 at Az of 0.882 and 0.926, respectively.…”
Section: Roc Analysismentioning
confidence: 96%
“…8 Many researchers applied this method to examine their image quality on different set of images with different number of reviewers and different types of diseases. 9,10,11 …”
Section: Subjective Evaluationmentioning
confidence: 99%
See 1 more Smart Citation